Communication, knowledge and the librarian - McGarry, K. J. (London : C. Bingley ; Hamden, Conn. : Linnet Books, 1975)
The author discusses , with reference different concepts, knowledge and historical development of communication and contemporary problems.
Includes bibliography and index.
kjo 17/01/2019
Loans
Keywords: Communication; Library science